Association between cytomegalovirus infection and allograft rejection in a large contemporary cohort of heart transplant recipients. Issue 4 (18th February 2021) - Boutolleau, David; Coutance, Guillaume; Désiré, Eva; Bouglé, Adrien; Bréchot, Nicolas; Leprince, Pascal; Varnous, Shaida
Abstract: Background: Cytomegalovirus (CMV) infection remains a common complication after heart transplantation (HTx). The association between CMV infection and allograft rejection is debated in the era of efficient prophylactic antiviral therapies. Methods: This single‐center cohort study utilized a highly phenotyped database of HTx recipients (2012‐2016). The primary endpoint was the analysis of the association between CMV infection (CMV load ≥ 500 IU/mL whole blood) and the risk of allograft rejection (cellular rejection ≥ 1R1B, antibody‐mediated rejection ≥ pAMR1). Secondary endpoints included the analysis of a higher CMV load threshold (≥10 000 IU/mL) and different risk periods after PCR positivity. A mixed‐effect logistic regression model with a random intercept was applied. Results were adjusted for important risk factors of rejection. Results: Overall, 384 patients were included and 6388 CMV loads and 3, 494 endomyocardial biopsies were analyzed. CMV infections ≥ 500 IU/mL were diagnosed on 1223 (19.2%) blood samples from 284 (72.1%) patients and allograft rejections on 246 biopsies (7%) from 149 patients (38.8%). We did not find any association between CMV infection ≥ 500 IU/mL and rejection (univariable: OR 0.94, 95% CI [0.61, 1.45], P  = .78, multivariable: OR 0.86, 95% CI [0.55, 1.33], P  = .85). These results were consistent when analyzing a higher CMV load threshold and different periods of risk, reinforced by internal validation procedures and a posteriori calculation of the power (primary endpoint: power = 0.82, 95% CI [0.79‐0.84]) and reproducible across different clinical scenarios. Conclusions: CMV infection was not associated with an increased risk of rejection in a contemporary cohort of HTx recipients.